The Influence of Sangkaropi' and Sandblasting Mining Aggregate on Concrete - Mikel Paa; Frans Phengkarsa; Lisa Febriani (Paulus Civil Engineering Journal, 2022)
Concrete is a composite building material made from a combination of aggregate and cement binder. The most common form of concrete is Portland cement concrete, which is composed of mineral aggregate, cement and water. It is usually believed that concrete dries after mixing and laying. In increasing the strength or quality of concrete, the coarse aggregate used comes from the Sangkaropi mine because in addition to the rare use of aggregate there, the Sangkaropi mine stone also contains minerals such as calcium oxide, silica dioxide, aluminum oxide. By adding materials, both in coarse aggregate and fine aggregate, as a substitute for binders and some as additional materials to increase the adhesion of binders in concrete, one of them is using sandblasting material in the concrete mixture. This is because sandblasting is a natural material whose raw materials contain less than 0.1 percent almandite and silica, which means that sandblasting does not contain hazardous and toxic materials (B3). The variations used are 0%, 5%, and 10%. The tests carried out were the compressive strength test, split tensile strength test, and the flexural strength test with a concrete quality of 25 MPa. From the results of this study, the compressive strength values ​​were 26.502 Mpa, 28.389 Mpa and 31.878 Mpa. In the split tensile strength test, the values ​​obtained were 1.721 Mpa, 2.146 Mpa, 2.617 Mpa and the flexural strength test obtained values ​​of 1.837 Mpa, 2.341 MPa, and 2,696 MPa.